Health Transformation at Asy-Syifa' Islamic Boarding School: Evidence from a Self-Assessment Survey - ALFA RIDHO, SYEIKHU; RAHMA WINDAYATI, DELLA; IMRON ROSADI, MUHAMMAD; BUDIYANTO, RULY; ADRIYAN, FAHMI (Tarqabin Nusantara Group, 2025)
Empowering pesantren communities is a strategic approach to improving health quality in environments that often face challenges such as anemia, poor clean and healthy living behavior (PHBS), and inadequate environmental sanitation. This study was conducted at Pesantren Tahfidzul Qur'an Putri Asy-Syifa', Malang City, aiming to increase students’ awareness and healthy behaviors through self-assessment surveys (Survei Mawas Diri/SMD) and educational interventions. A total of 30 female students aged 12–18 years participated in the study, which consisted of surveys, group discussions, and health education-based interventions. The SMD results identified anemia as the top health issue based on the USG (Urgency, Seriousness, Growth) matrix. Interventions included